1983
DOI: 10.3354/meps011023
|View full text |Cite
|
Sign up to set email alerts
|

Role of a natural disturbance in an assemblage of marine free-living nematodes

Abstract: One of the predictions of theoretical treatments of soft-bottom benthos is: if disturbance were responsible for the persistence of a species in a community, that species should become disproportionately abundant in recently disturbed patches. We investigated this predict~on using marine free-living nematode species in subtidal (2 to 3 m depth) sediments off the Florida panhandle (2g054.55'N, 84"31.45'W), frequently disturbed by stingrays (Dasyatis sabina). In disturbed sediments nematode densities gradually in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…Some studies have shown that nematodes can be quite resilient to pollution, with small or no changes in assemblage structure when perturbed (Alongi et al 1983, Gee et al 1985, Lambshead 1986, Warwick et al 1988. This also applies to some studies on biological disturbance (Sherman et al 1983), though in other cases significant differences have been found (Warwick et al 1986, Warwick et al 1990.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Some studies have shown that nematodes can be quite resilient to pollution, with small or no changes in assemblage structure when perturbed (Alongi et al 1983, Gee et al 1985, Lambshead 1986, Warwick et al 1988. This also applies to some studies on biological disturbance (Sherman et al 1983), though in other cases significant differences have been found (Warwick et al 1986, Warwick et al 1990.…”
Section: Discussionmentioning
confidence: 91%
“…The activities of the macrofauna are a source of disturbance which may influence the structure of meiofaunal assemblages (Reise & Ax 1979, Thistle 1980, Reidenauer & Thistle 1981, Sherman et al 1983, Creed & Coull 1984, Hicks 1984, Warwick et al 1986, Palmer 1988, Warwick et al 1990, , , Sundelin & Elmgren 1991. However, there are few reports on experiments where the intensity of biological disturbance has been graded into O Inter-Research/Printed in Germany more than 2 categories, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In finding that meiofaunal abundances on an artificially disturbed intertidal mudbank rapidly returned to ambient levels within the space of one tidal cycle (12 h), Sherman & Coull (1980) suggested that incoming recruits to the disturbed patch did so by either active mobility over the sediment surface, or passively via tidal transport in the water column. These 2 pathways have repeatedly been invoked as those of importance in the rapid reestablishment of meiofaunal densities in habitats either naturally disturbed or artificially manipulated (Bell & Sherman 1980, Thistle 1980, Hockin & Ollason 1981, Reidenauer & Thistle 1981, Bell & Coen 1982, Van Blaricom 1982, Alongi et al 1983, Chandler & Fleeger 1983, Sherman et al 1983, Ambrose 1986. Results from reports by Palmer (1984, and subsequently with co-workers), have added considerable weight to the passive erosional method of entry into the water column with subsequent transport and supposed recolonization of viable meiofaunal propagules.…”
Section: Distance Travelled By Rafts Fate Of Rafted Populationmentioning
confidence: 94%
“…For example, by hydraulically jetting water from the mouth or gills (Gregory et al 1979, Sasko et al 2006), some batoids can create feeding pits up to 40cm deep (Smith and Merriner 1985). In areas frequented by batoids, approximately 1% (but with maximums up to about 5%) of the area can be covered by new foraging pits per day (Reidenauer and Thistle 1981, VanBlaricom 1982, Sherman et al 1983) and foraging pits of various ages cover up to 30% of some areas . Given that even small-scale resuspension events, such as those caused by benthic fishes, have profound effects on the reworking of the substrate surface (Yahel et al 2002), benthic foraging elasmobranchs may play an important role in nutrient dynamics of at least some systems.…”
Section: Elasmobranch Impacts On Nutrient Dynamicsmentioning
confidence: 99%
“…Such foraging excavations, especially in areas of high elasmobranch density, can result in the turnover of large volumes of sediment. Several studies have shown that in areas frequented by batoids, new foraging pits cover can cover 1-5% of the substrate each day (Reidenauer and Thistle 1981, VanBlaricom 1982, Sherman et al 1983) and up to 30% of the substrate can be covered with foraging pits of various ages . Over time this can result in considerable sediment turnover.…”
Section: Unvegetated Soft Bottommentioning
confidence: 99%